Reversed-phase high-performance liquid chromatography fingerprint profiles of thirty-nine mosses with chemometric - Hawrył, Anna; Bogucka-Kocka, Anna; Świeboda, Ryszard; Hawrył, Mirosław; Stebel, Adam (Journal of liquid chromatography & related technologies, 2017)
Thirty-nine land and aquatic mosses were extracted by double maceration and ultrasonic extraction techniques using the mixture of 80% ethanol and water. Obtained extracts were analyzed using the reversed-phase-high-performance liquid chromatography-diode array detector with the Kinetex C18 chromatographic column and mobile phase consisting of acetonitrile-water-0.1% formic acid mixture (gradient 5-100%, 60 min) with detection wavelength of 280 nm. Next, obtained chromatograms were preliminary processed with the smoothing, noise reduction, background subtraction, and alignment using the SpecAlign program (version 2.4.1). The chemometric analysis was performed to obtain the fingerprint chromatograms of selected mosses. The principal component analysis and the cluster analysis (with paired group algorithm and correlation coefficient-r, as similarity measure) confirm the chemical similarity or differences between studied Bryophyta sp.